A nation‐wide survey of neonicotinoid insecticides in agricultural land with implications for agri‐environment schemes. Issue 7 (2nd May 2019) - Humann‐Guilleminot, Ségolène; Binkowski, Łukasz J.; Jenni, Lukas; Hilke, Gabriele; Glauser, Gaétan; Helfenstein, Fabrice
Abstract: Neonicotinoids are the most widely used class of insecticides globally. However, the link between farming practices and the extent of contamination of soils and crops by neonicotinoid insecticides, as well as the extent of such contamination in organic fields and ecological focus areas (EFAs) are currently unclear. We measured the concentrations of five neonicotinoid insecticides (imidacloprid, clothianidin, thiamethoxam, thiacloprid, acetamiprid) in 702 soil and plant samples in 169 cultivated fields and EFAs from 62 conventional, integrated production and organic farms distributed over the entire lowland of Switzerland. We detected neonicotinoids in 93% of organic soils and crops, and more than 80% of EFA soils and plants—two types of arable land supposedly free of insecticides. We also tested 16 samples of organic seeds, of which 14 were positive for neonicotinoids. Finally, we calculated hazard quotients (HQs) and potentially affected fractions for 72 beneficial and 12 pest species. Under a field‐realistic scenario, we found that between 5.3%–8.6% of above‐ground invertebrate species may be exposed to lethal concentrations of clothianidin, and 31.6%–41.2% to sublethal concentrations, in "integrated production" and conventional fields. We also found that 1.3%–6.8% (up to 12.5% based on HQs) of the beneficial invertebrate species may be exposed to sublethal concentrations of neonicotinoids in EFAs and organic fields. In contrast, no pest species would be exposed to lethal concentrations, even under a worst‐case scenario. Synthesis and applications . Our study suggests that diffuse contamination by neonicotinoids may harm a significant fraction of non‐target beneficial species. The use of neonicotinoids on crops may threaten biodiversity in refuge areas, while also potentially jeopardizing the practice of organic farming by impeding the biological control of pests. On the basis of our results, we call for a reduction in the dispersion and overuse of neonicotinoid insecticides in order to prevent any detrimental effects on biodiversity and ecosystem services associated with agroecosystems. Abstract : Our study suggests that diffuse contamination by neonicotinoids may harm a significant fraction of non‐target beneficial species. The use of neonicotinoids on crops may threaten biodiversity in refuge areas, while also potentially jeopardizing the practice of organic farming by impeding the biological control of pests. On the basis of our results, we call for a reduction in the dispersion and overuse of neonicotinoid insecticides in order to prevent any detrimental effects on biodiversity and ecosystem services associated with agroecosystems. Editor's Choice ZUSAMMENFASSUNG: Neonicotinoide sind weltweit die am meisten verbreitete Gruppe von Insektiziden. Es ist jedoch unklar inwiefern ein Zusammenhang zwischen den landwirtschaftlichen Praktiken und dem Ausmass der Kontimination von Böden und Erntegut durch Neonicotinoide besteht. Über das Ausmass einer solchen Kontamination auf biologischen Feldern und Ökologischen Ausgleichsflächen (ÖAF) ist ebenfall wenig bekannt. Wir haben die Konzentrationen von fünf Neonicotinoid Insektiziden (Imidacloprid, Clothianidin, Thiamethoxam, Thiacloprid, Acetamiprid) in 702 Boden‐ und Pflanzenproben von 169 Ackerflächen und ÖAF von 62 konventionellen, IP (Integrierter Landbau) und biologischen Landwirtschaftsbetrieben im schweizer Mittelland gemessen. Auf 93% der Böden und des Ernteguts der biologischen Betriebe als auch auf über 80% der Böden und Pflanzen der ÖAF haben wir Neonicotinoide festgestellt—zwei Arten von landwirtschaftlichen Flächen, welche vermeintlich frei von Insektiziden sein sollten. Wir haben ebenfalls 16 Proben von biologischem Saatgut untersucht, von denen 14 Neonicotinoide enthielten. Schliesslich haben wir den Gefahrenquotienten (GQ) und den potentiel betroffenen Anteil von 72 Nützlingen und 12 Schädlingen berechnet. In einem feldrealistischen Szenario haben wir festgestellt, dass zwischen 5, 3 bis 8, 6% der oberirdischen Wirbellosenarten tödlichen Konzentrationen von Clothianidin und 31, 6 bis 41, 2% subletalen Konzentrationen in der IP‐ und konventionellen Feldern ausgesetzt sein können. Wir haben ebefalls festgestellt, dass 1, 3 bis 6, 8% (bis zu 12, 5% basierend auf GQ) der Nützlinge subletalen Konzentrationen von Neonicotinoiden in ÖAF und biologischen Feldern ausgesetzt sein können. Im Gegensatz dazu würden Schädlinge selbst im schlimmsten Szenario keiner tödlichen Konzentration ausgesetzt sein. Synthese und Anwendungen . Unsere Studie deutet darauf hin, dass eine diffuse Kontamination durch Neonicotinoide einen erheblichen Teil der nicht zu den Zielgruppen gehörenden Nützlingen schädigen kann. Die Verwendung von Neonicotinoiden auf Ackerflächen kann die biologische Vielfalt in Rückzugsgebieten bedrohen und gleichzeitig den biologischen Landbau gefährden, indem sie die biologische Schädlingsbekämpfung behindert. Auf Grundlage unserer Ergebnisse fordern wir eine Verringerung der Verbreitung und des übermäßigen Einsatzes von Neonicotinoid‐Insektiziden, um schädliche Auswirkungen auf die Biodiversität und die mit Agrarökosystemen verbundenen Ökosystemleistungen zu vermeiden.